Rotational thromboelastometry reduces blood loss and blood product usage after lung transplantation - Durila, Miroslav; Vajter, Jaromir; Garaj, Michal; Pollert, Lukas; Berousek, Jan; Vachtenheim, Jiri; Vymazal, Tomas; Lischke, Robert (The Journal of heart and lung transplantation, 2021)
BACKGROUND: The shortage of blood products has become a worldwide problem, especially during the COVID-19 Pandemic. Here, we investigated whether a point of care (POC) approach to perioperative bleeding and coagulopathy based on rotational thromboelastometry (ROTEM) results could decrease perioperative blood loss and the perioperative consumption of blood products during lung transplantation. METHODS: Patients undergoing bilateral lung transplantation were randomized into two groups: In the first group, designated the "non POC" group, the management of perioperative bleeding and coagulopathy was based on the clinical experience of the anesthesiologist; in the second group, designated the "POC" group, the management of perioperative bleeding, and coagulopathy was based on the ROTEM results. RESULTS: After performing an interim statistical analysis, the project was prematurely terminated as the results were significantly in favor of the POC approach. Data were analyzed for the period January 2018 until June 2020 when 67 patients were recruited into the study. There was significantly decreased perioperative blood loss in the POC group (n = 31 patients) with p = 0.013, decreased perioperative consumption of RBC with p = 0.009, and decreased perioperative consumption of fresh frozen plasma with p < 0.0001 (practically no fresh frozen plasma was used in the POC group) without deteriorating clot formation in secondary and primary hemostasis as compared to the non POC group (n = 36). CONCLUSION: POC management of perioperative bleeding and coagulopathy based on ROTEM results is a promising strategy to decrease perioperative blood loss and the consumption of blood products in lung transplantation.
Keywords: Hemostasis; Male; Middle Aged; transplantace plic; bleeding; Blood Transfusion; hemostáza; transplantation; koagulopatie; tromboelastografie; mužské pohlaví; pandemie; krevní transfuze; SARS-CoV-2; lidé; ženské pohlaví; Thrombelastography; Humans; point of care; Lung Transplantation; Blood Coagulation Disorders; Pandemics; blood transfusion products; Female; lidé středního věku; ROTEM; COVID-19